Epistemologi Jadali dalam Tradisi Islam dan Relevansinya bagi Rasionalisme Modern - Mutia Ummi Fadhillah; Ulya Putri Alfarida; Musa (CV. Doki Course and Training, 2025)
Jadali epistemology represents one of the foundational pillars of the Islamic intellectual tradition, emphasizing the pursuit of truth through dialogue, rational argumentation, and coherence with divine revelation. Originating from the concept of mujadalah, Jadali evolved into a method of reasoning designed to test, refine, and authenticate arguments through sound logic and strong textual grounding. This article provides an in-depth examination of the Jadali mode of thought, including its dialogical, comparative, and critical methods, as well as the contributions of key figures such as Al-Ghazali and Fakhruddin al-Razi in strengthening the rational paradigm within Islamic scholarship. The study also compares Jadali epistemology with Western rationalism as developed by thinkers like René Descartes and Immanuel Kant. Although both traditions highlight the central role of reason, they differ fundamentally in their epistemological orientations: Western rationalism tends to be individualistic and introspective, whereas Jadali is dialogical, intersubjective, and firmly anchored in revelation. Through a qualitative library-based approach, this research demonstrates that Jadali epistemology offers a more holistic, ethical, and integrated model of knowledge, making it highly relevant for contemporary Islamic education and the cultivation of critical thinking in the modern era.